Co-education in the teaching of technical sciences in higher education (Eurasian Journal of Learning and Academic Teaching, 2023)
The article provides experience in the implementation of innovative types of training, which is used in the process of teaching technical disciplines. The paper reflects innovative forms of education that will allow teachers to more activate the cognitive activity of students.